Penerapan Retorika Aristoteles sebagai Strategi Persuasi Pesan Layanan Masyarakat oleh Gen Alpha: Kegiatan Abdimas di SMA Fons Vitae 1 Jakarta - Putri Rindu Kinasih (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
The use of persuasion theory is extremely important in daily life. Persuasion is crucial in situations other than marketing campaigns or political campaigns. Disseminating information to the general public and researching shifts in social norms and values both require persuasion. Aristotle's rhetorical triangle—ethos, pathos, and logos—is one of the persuasive techniques that have a significant impact on the communication industry. Aristotle's rhetorical triangle has been the subject of numerous studies, but few have addressed the problem of message delivery, particularly in digital public service announcements. The writer was encouraged to hold an ABDIMAS activity entitled "The application of Aristotle's rhetoric as a persuasive strategy for public service messages by Gen Alpha" at SMA Fons Vitae 1 Matraman, East Jakarta. The participants who attended were 22 people, 11 men, and 11 women, a combination of students from grades X to XII who were members of the English Club. The ABDIMAS activity which was held on Thursday, March 13, 2025, combined lecture technique and direct practice. From the results of the practice, it was found that all participants were able to apply Aristotle's rhetorical triangle persuasion strategy, with the most dominant strategy used being logos.